2012
DOI: 10.12717/dr.2012.16.4.379
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of LHX8 DNA Binding Elements

Abstract: Lhx8 (LIM homeobox 8) gene encodes a LIM homeodomain transcriptional regulator that is preferentially expressed in germ cells and critical for mammalian folliculogenesis. However, Lhx8 DNA binding sequences are not characterized yet. We aimed to identify and characterize a cis-acting sequence of germ-cell specific transcriptional factor, Lhx8. To identify Lhx8 DNA binding element, Cyclic Amplification of Sequence Target (CAST) Analysis was performed. Electrophoretic Mobility Shift Assay (EMSA) was processed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Consistent with its function in meiosis, in Lhx8-/-ovaries we observed dysregulation of Msx1, a gene involved in promoting meiosis [49] and identified as a putative target of LHX8 [11] (Figure 2G), and another initiator of meiosis, Stra8, was earlier reported to be upregulated [10]. Furthermore, SPO11, directly involved in the induction of DNA breaks for recombination during meiosis [50], was also dysregulated at P0 in Lhx8-/-ovaries ( Figure 2G); thus, significant DNA damage was still ongoing at that stage.…”
Section: Dna Damage and Autophagysupporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with its function in meiosis, in Lhx8-/-ovaries we observed dysregulation of Msx1, a gene involved in promoting meiosis [49] and identified as a putative target of LHX8 [11] (Figure 2G), and another initiator of meiosis, Stra8, was earlier reported to be upregulated [10]. Furthermore, SPO11, directly involved in the induction of DNA breaks for recombination during meiosis [50], was also dysregulated at P0 in Lhx8-/-ovaries ( Figure 2G); thus, significant DNA damage was still ongoing at that stage.…”
Section: Dna Damage and Autophagysupporting
confidence: 78%
“…Recent in vitro analyses have identified TGATTG as the core of a putative LHX8 DNA-binding sequence and showed that LHX8 directly regulates the transcription of several genes including germ cell-specific Nobox [11]. The mechanism of action of Lhx8 and the cause of oocyte death in its absence have, however, been unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Based on bioinformatics analysis and promoter deletion analysis of this study, we found that within the −427 to −376 bp region of the pig BMP15 promoter there exists sites for transcription factors LHX8, NOBOX, and PITX1, which are the potential positive regulators to activate pig BMP15 . Although LHX8 , NOBOX , BMP15, and GDF9 are highly expressed during ovarian follicle development [ 25 , 35 ], the definite regulatory network among these genes is under investigation. Several studies have reported an association between the BMP15 and premature ovarian failure, showing that the variant BMP15 c.-9 C>G results in modification of its binding sites for PITX1 that trans-activates BMP15 promoter and increases the recruitment of an elevated number of follicles/oocytes early in a woman’s life [ 18 , 30 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic neurons are derived from progenitor cells in the MGE, where LHX8 promotes the expression of Isl1 upon cholinergic commitment, which in turn represses Lhx6 expression ( Zhao et al, 2003 ). Lhx8 forms a hexamer with Isl1 and promotes cholinergic neuron expression by binding to specific motifs in the cholinergic enhancer sequence ( Park et al, 2012 ). The formation of hexamers is necessary for DNA binding and subsequently cholinergic gene expression, whilst LHX8 or ISL1 alone does not bind to cholinergic enhancer sequences and are unable to promote cholinergic interneuron differentiation ( Cho et al, 2014 ).…”
Section: Selected Transcription Factors Encoded By Homeobox Genesmentioning
confidence: 99%